Simultaneous Supplementation of Bacillus subtilis and Antibiotic Growth Promoters by Stages Improved Intestinal Function of Pullets by Altering Gut Microbiota - Li, Xueyuan; Wu, Shengru; Li, Xinyi; Yan, Tao; Duan, Yongle; Yang, Xin; Duan, Yulan; Sun, Qingzhu; Yang, Xiaojun (Frontiers in Microbiology, 2018)
The effects of simultaneously short-termed supplementation of AGPs (Bacitracin Zinc 20 mg/kg and Colistin Sulphate 4 mg/kg) and Bacillus Subtilis (B.subtilis) DSM17299, as well as the effects of supplementation of AGPs in the whole 16 weeks on the overall growth and development, intestinal health, and caecal microbiota of pullets were evaluated. 630 one-day-old Hy-Line Brown layers were randomly distributed into five equal groups: including the AGPs group (supplemented with AGPs for 16 weeks), the BA3 group (supplemented with AGPs and B.subtilis for 3 weeks), the BA6 group (for 6 weeks), the BA12 group (for 12 weeks), and the BA16 group (for 16 weeks). When compared with the AGPs group, the supplementation of AGPs + B.subtilis for first 3 weeks could maintain overall growth performance, including the average body weight, average feed intake, average daily weight gain, and feed conversion ratio of pullets (P>0.05). Meanwhile, at 3weeks of age, the amylase activity in ileum was significantly elevated (P=0.028) in BA3 group. At 12 weeks of age, the significantly increased villus height (P=0.046) of jejunum, significantly increased villus height (P=0.023) and ratio of villus height to crypt depth (P=0.012) of ileum, significantly decreased crypt depth (P=0.002) of ileum, and significantly elevated mRNA levels of sucrase in jejunum (P<0.05) were all identified in BA3 group. At 16 weeks of age, the jejunal sIgA content of BA3 group was higher than other groups (P<0.001). Furthermore, significantly decreased Alistipes, Bacteroides, Odoribacter, Dehalobacterium, and Sutterella, as well as increased Lactobacillus, Dorea, Ruminococcus, and Oscillospira were determined (P<0.05) in BA3 group at week 6. Meanwhile, the significantly decreased B. fragilis and C. leptum (P<0.05) were identified in BA3 group at week 12, which were significantly positively relevant to the improvement of intestinal morphology by Pearson analysis. In conclusion, simultaneous supplementation of AGP and B. subtilis for 0~3 weeks increased the relative abundance of beneficial microbiota in caecum in 0~6 weeks, then improved intestinal morphology by elevating populations of B. fragilis and C. leptum in 7~16 weeks, and further promoted intestinal morphology, up-regulate sucrase expression, and increase sIgA content in intestinal mucosa in 13~16 weeks.